KOMPETENSI MANAJERIAL PEJABAT PENGAWAS DALAM PERSPEKTIF PEJABAT PELAKSANA DI BADAN PENDAPATAN DAERAH KABUPATEN DONGGALA - Vivi Indra Amelia Nasution; Mieke Arianthi; Ridho Harta (Jurnal Ilmiah Wahana Bhakti Praja, 2024)
This study aims to determine the level of managerial competency of Supervisory Officers at the Regional Revenue Agency of Donggala Regency which is based on the Competency Standards for ASN Positions as stipulated in the Regulation of the Minister of Administrative Reform and Bureaucratic Reform Number 38 of 2017, through the perceptions of Implementing Officials. The research was conducted using a qualitative descriptive approach to provide an overview of the managerial competence of Supervisory Officers through the perceptions of Implementing Officers. This research is a case study research and is supported by data sourced from interviews, observations, and documentation. Interviews were conducted using purposive sampling by determining key informants. There were eleven Executive Officers who were interviewed to see how the managerial competence of the six Supervisory Officers in the Regional Revenue Agency of Donggala Regency was. The results showed that most of the Supervisory Officers had not been able to fulfill five of the eight indicators of level two managerial competency according to the behavior indicators that Supervisory Officers must possess. The indicators of managerial competence that have not been fulfilled are result orientation, managing change, public service, integrity, and decision making. Meanwhile, indicators of communication, cooperation, as well as self-development and that of others, are perceived very well by the Executive Officers.